Meta-Analisis Landasan Ilmu Pendidikan Pada Pengembangan E-Book Edupark Fisika Berdasarkan Destinasi Pantai Padang - ELvisa, Gita Oktia; Festiyed, Festiyed (Universitas Negeri Padang, 2019)
Education is demanded to keep abreast of rapidly developing technology and utilize information and communication technology as more and more sophisticated facilities to facilitate the learning process. One that must be prepared by educators in the learning process is learning resources. Learning resources related to everything that allows students to experience the learning process. Physics is closely related to natural phenomena and their application in everyday life. Learning physics is more meaningful if you observe directly. The beach is one of the natural phenomena which is a physical concept that can be observed directly. The beach is a tourist destination for domestic and foreign tourists that can be used as edupark in the physics learning process. Edupark is an educational park that should be able to be used by educators as a source of learning for students. However, educators rarely use beach tourism as a learning resource. Utilization of local tourist destinations can be used in learning physics by implementing the development of science and technology that are developing now. According to the needs of students, so that information technology-based teaching materials can be used in the form of e-books. The use of e-books aims to help students understand the concepts of physics found on the beach. This research method is a meta-analysis with a sample of 20 international and national artists. This meta-analysis aims to analyze the interrelationship of educational science foundations in the development of Physics e-books.